2003
DOI: 10.1073/pnas.2136756100
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus latent membrane protein 1 activation of NF-κB through IRAK1 and TRAF6

Abstract: Epstein–Barr virus latent membrane protein 1 (LMP1) activation of NF-κB is critical for Epstein–Barr virus-infected B lymphocyte survival. LMP1 activates the IκB kinase complex and NF-κB through two cytoplasmic signaling domains that engage tumor necrosis factor receptor-associated factor (TRAF)1/2/3/5 or TRADD and RIP. We now use cells lacking expression of TRAF2, TRAF5, TRAF6, IKKα, IKKβ, IKKγ, TAB2, IL-1 receptor-associated kinase (IRAK)1, or IRAK4 to assess their roles in LMP1-mediated NF-κB activation. LM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
4
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 58 publications
4
153
4
1
Order By: Relevance
“…Fourth, LMP1-stimulated JNK activation is unaffected in TRAF2 Ϫ/Ϫ mouse embryonic fibroblasts (MEFs) (41). Finally, LMP1-induced NF-B activation is nearly normal in TRAF2 and TRAF5 double-knockout MEFs (48). Thus, the preponderance of accumulating evidence indicates that TRAF2 does not play essential, nonredundant roles in key LMP1-mediated activation events in B cells and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, LMP1-stimulated JNK activation is unaffected in TRAF2 Ϫ/Ϫ mouse embryonic fibroblasts (MEFs) (41). Finally, LMP1-induced NF-B activation is nearly normal in TRAF2 and TRAF5 double-knockout MEFs (48). Thus, the preponderance of accumulating evidence indicates that TRAF2 does not play essential, nonredundant roles in key LMP1-mediated activation events in B cells and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional roles of TRAF5 in LMP1-mediated signaling remain to be determined. Although it has been previously shown that overexpression of dominant-negative TRAF5 abrogates CTAR1-mediated NF-B activation (5), it was recently found that LMP1-induced NF-B activation is nearly normal in TRAF2 and TRAF5 double-knockout MEFs (48). Interestingly, recent studies reported that both JNK activation and NF-B activation mediated by LMP1 signaling are severely impaired in TRAF6 Ϫ/Ϫ MEFs, suggesting an indispensable role for TRAF6 in LMP1 signaling in fibroblasts (41,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of recent publications suggest that TRAF2 has a key role in CD40 activation of the JNK and NF-KB pathways, whereas it seems to have only a marginal role in the activation of the same pathways by LMP1. 7,44,45,46 This would suggest that TRAF2 association with buoyant complexes is linked in some way with its contribution to JNK and NF-KB cascades. On the other hand, a binding of TRAF2 to LMP1 in vivo is well documented in several types of cell contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, activation of NF-kB by the latent membrane protein 1 (LMP1) of the human Herpesvirus Epstein-Barr virus (EBV), implicated in Burkitt's lymphoma, is critical for transformation of human B cells (Cahir-McFarland et al, 2000;Feuillard et al, 2000;He et al, 2000;reviewed in Hiscott et al, 2006). Recent work implicates interleukin-1b receptorassociated kinase 1 (IRAK1) and TRAF6 in NF-kB activation via latent membrane protein 1 (LMP1) and in phosphorylation of the RelA transactivation domain (Luftig et al, 2003;Song et al, 2006;Wu et al, 2006). A second study has reported that activation of the noncanonical NF-kB pathway, leading to accumulation of nuclear p52/RelB complexes, is required for LMP-1-mediated transformation of human B cells (Luftig et al, 2004).…”
Section: Update On Nf-jb's Protective Activity Following Viral Infectmentioning
confidence: 99%